EKSISTENSI NASAKH DALAM IMPLEMENTASI ELASTISITAS HUKUM ISLAM - Khatib, Suansar (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2014)
In a view of Muslim scholars, naskh(abrogation) is one of the metods in undertaking ta`ârudh al-Adillah. Nevertheles, there are disputes on meaningand existence of naskh in the Qur’an and Hadis and the influence in applying istinbath al-hukm (deducing Islamiclaw) among them. The present paper is aimed at describing the function of naskh as one of the elsaticityelements in the Islamic law. In developing islamic law, to appear the elasticity, the real meaning of naskh is toabrogate a law from a side to another one. Naskh, on the other hand, also stands for tentative abrogation and itcan be applied recently in other way based on apropriate situation, condition, and motivation